2016
DOI: 10.1128/jvi.02096-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Serine-Rich Tract of Varicella-Zoster Virus IE62

Abstract: The immediate early 62 protein (IE62) of varicella-zoster virus (VZV), a major viral trans-activator, initiates the virus life cycle and is a key component of pathogenesis. The IE62 possesses several domains essential for trans-activation, including an acidic trans-activation domain (TAD), a serine-rich tract (SRT), and binding domains for USF, TFIIB, and TATA box binding protein (TBP). Transient-transfection assays showed that the VZV IE62 lacking the SRT trans-activated the early VZV ORF61 promoter at only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…VZV IE62 possesses an acidic transactivation domain (TAD), a serine-rich tract (SRT), and binding domains for DNA and TATA-binding protein (TBP) (39,(53)(54)(55)(56). IE62, a tegument protein, binds several viral proteins, such as ORF4 (57), ORF9 (58), ORF47 (59), and ORF63 (60), as well as cellular transcription factors, including upstream stimulatory factor (USF), TBP, mediator 25, and Sp1 (39,54,(61)(62)(63)(64)(65). Our recent studies showed that IE62 SRT is necessary for TAD-mediated transactivation and that the TAD and SRT of VZV IE62 interact with the cellular transcriptional coactivator mediator 25 and nucleolar-ribosomal EAP, respectively (54).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…VZV IE62 possesses an acidic transactivation domain (TAD), a serine-rich tract (SRT), and binding domains for DNA and TATA-binding protein (TBP) (39,(53)(54)(55)(56). IE62, a tegument protein, binds several viral proteins, such as ORF4 (57), ORF9 (58), ORF47 (59), and ORF63 (60), as well as cellular transcription factors, including upstream stimulatory factor (USF), TBP, mediator 25, and Sp1 (39,54,(61)(62)(63)(64)(65). Our recent studies showed that IE62 SRT is necessary for TAD-mediated transactivation and that the TAD and SRT of VZV IE62 interact with the cellular transcriptional coactivator mediator 25 and nucleolar-ribosomal EAP, respectively (54).…”
Section: Discussionmentioning
confidence: 99%
“…IE62, a tegument protein, binds several viral proteins, such as ORF4 (57), ORF9 (58), ORF47 (59), and ORF63 (60), as well as cellular transcription factors, including upstream stimulatory factor (USF), TBP, mediator 25, and Sp1 (39,54,(61)(62)(63)(64)(65). Our recent studies showed that IE62 SRT is necessary for TAD-mediated transactivation and that the TAD and SRT of VZV IE62 interact with the cellular transcriptional coactivator mediator 25 and nucleolar-ribosomal EAP, respectively (54). The SRT is necessary for the formation of large globular structures within the nucleus (54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that ISG15 functions as an antiviral molecule against EHV-1, but its mechanism of action, as well as the identity of the EHV-1 molecules that induce ISG15, remains to be determined. In this regard, comparison of alphaherpesvirus genomes showed that varicellazoster virus, pseudorabies virus, and HSV-1 are similar in structure to EHV-1 and that each of these viruses encodes a protein that shares extensive homology with the EHV-1 immediate early protein (65,66). Infection with EHV-1 wild-type strain Ab4 reduced IFN-␥ production in primary equine respiratory epithelial cells (67).…”
Section: Discussionmentioning
confidence: 99%